A continuum‐approach modeling of surface composition and ternary component distribution inside low fat milk emulsions during single droplet drying. Issue 7 (6th February 2017) - Putranto, Aditya; Foerster, Martin; Woo, Meng Wai; Selomulya, Cordelia; Chen, Xiao Dong
Abstract : Surface composition of dairy powders plays an important role in determining the functionality. However, the surface composition may be different from the bulk composition because of component migration during drying. In this study, a comprehensive mathematical model has been developed to describe the phenomena. To the best of our knowledge, it is the first mathematical model which predicts the dynamics of surface composition during drying. The model consists of a set of equations of conservation of mass of water, lactose, protein, and fat as well as conservation of heat and momentum in which the effects of diffusion induced material migration and surface activity are incorporated. This model is applicable to describe the kinetics of surface composition of dairy droplets during drying. It suggests that both diffusion and protein surface activity govern the component segregation during drying. The study indicates that the model implementing the measured initial surface composition as the initial conditions generates more realistic profiles than the one using the bulk composition. The modeling confirms that the difference between the surface and bulk composition that occurs prior to drying is not primarily governed by diffusion, but the emulsion's atomization behavior seems to play an essential role in the overrepresentation of fat. © 2017 American Institute of Chemical Engineers AIChE J, 63: 2535–2545, 2017